PENERAPAN MODEL PEMBELAJARAN CORE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIPA SMAN 5 PADANG - Suhendri, Chantika Enza (Departemen Matematika, 2023)
Mathematical understanding concepts is a main skill that is fundamental to dealing with various problems in mathematics learning. But in actuality, the students ability remains at a low level. To solve this problem, the CORE learning model can be applied. This study intends to ascertained if the student’s mathematical concept comprehension skills who are learned with the CORE model are superior to those who are learned with the direct learning model in XI MIPA grade in SMAN 5 Padang. The selected samples were XI MIPA 1 students namely experimental group and XI MIPA 2 students namely comparison group. The results were analysed by t-test and indicated that the student’s mathematical concepts comprehension skills who are learned with the CORE model are superior to those who are learned with the direct learning model in XI MIPA grade in SMAN 5 Padang.Keywords– CORE, Mathematical Understanding Concepts